(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
The article is based on the materials of field mapping of surface loose formations and relief-forming processes on a scale of 1:25 000 of the Getik River basin. An analysis of the river basin network and the morphological features of its valley revealed a number of inconsistencies that contradict the current direction of the river. In the Late Pliocene-anthropogenic period, a significant restructuring of the river network took place here – the main river changed the direction of its flow from South-East to North-West. This restructuring is reflected by inconsistencies in the high order of the tributaries of the Getik River, the presence of multilevel terraces, the flat nature of the river with a meandering channel, traces of a paleolake with sufficiently thick lake clays in its modern upper reaches, which contradicts the geomorphological patterns of the river valley development. For the first time, the outlines of the paleolake, which was formed in front of the Chambarak pass, have been outlined. The current tectonic activity of the Getik River basin is emphasized by its high seismicity, the presence of deep and regional faults, and the widespread occurrence of numerous active landslides on both slopes of the main river valley and its tributaries.